PENGARUH KOMPENSASI TERHADAP KINERJA PEGAWAI BAGIAN PROTOKOL, KOMUNIKASI DAN TATA USAHA PIMPINAN DI SEKRETARIAT DAERAH - Rosi Pitria; Tuah Nur; M. Rijal Amirulloh (LPPM Universitas Djuanda Bogor, 2023)
The research conducted in the study focuses on the impact of compensation (X) on the performance (Y) of employees in the Protocol, Communication, and Administration division of the Regional Secretariat of Sukabumi City. Compensation was evaluated using Rivai's Theory (2018: 357), which includes direct financial compensation, such as salaries and incentives, and indirect compensation, such as allowances and facilities. On the other hand, performance was measured using Mangkunegara's Theory (2015: 68) based on three dimensions: quality, quantity, and responsibility. The research method employed was an associative method using a quantitative approach, and the data was collected through questionnaires and interviews. The sample size used in the research was obtained through a saturated sampling technique, and SPSS (Statistical Product and Service Solutions) 26 was used for data analysis. The data was analyzed to determine its validity, reliability, correlation coefficient, and the extent to which compensation affects employee performance through linear regression analysis. The findings of the analysis revealed a strong relationship between compensation and employee performance, with a correlation coefficient of 0.943 and a coefficient of determination of 88.92%. Based on the results, the hypothesis that compensation has a positive impact on employee performance in the Protocol, Communication, and Administration division of the Regional Secretariat of Sukabumi City was accepted. Therefore, the study concludes that compensation has an optimal impact on employee performance, and there is a positive relationship between compensation and employee performance in this division.